Suppressive effect of globin digest on postprandial hyperlipidermia in male volunteers - Kagawa, K. (Kyoei Bussan Company, Osaka, Japan.); Matsutaka, H; Fukuhama, C; Fujino, H; Okuda, H (The Journal of nutrition, 1998)
We have reported previously that various edible protein digests inhibit dietary hyperlipidemia in mice, rats, pigs and dogs. Of the various digests tested, globin digest had the most potent inhibitory activity, and a tetrapeptide extracted from globin digest, Val-Val-Tyr-Pro, had activity 7000-fold greater than that of the parent digest. In this clinical study, we investigated the influence of globin digest on serum chylomicron triglyceride concentrations as an indicator of the effect ot globin digest on fat absorption and catabolism in humans. Parallel and crossover trials were conducted in which men consumed a control high fat diet (25 g fat, 7.6 g carbohydrate, 1.9 g protein and 0.7 g sodium chloride) or the same diet supplemented with globin digest. The supplemented dosages were 1 and 4 g globin digest. In the parallel trial, 22 men were divided into three groups: control, globin digest 1 g and globin digest 4 g. The increases in chylomicron triglyceride concentrations at 1 h after ingestion of 1 or 4 g globin digest were significantly lower (P 0.05) compared with the control group. The crossover trial involved six subjects who consumed the control high fat diet and the same diet supplemented with 4 g globin digest. Serum chylomicron triglyceride levels increased in both groups at 1 and 2 h after ingestion, but when subjects consumed 4 g globin digest the increases were suppressed to 75 (P 0.05) and 42% (P 0.05) of the increases in controls at the corresponding times, respectively. The areas under the curves of chylomicron and serum total triglyceride concentrations during the 4 h after ingestion of 4 g globin digest were 46 (P 0.05) and 34% (P 0.05) lower, respectively, than when the men consumed the high fat control diet. In these trials, globin digest reduced the increase in serum chylomicron triglyceride concentrations as a result of the ingestion of a high fat diet. This hypotriglyceridemic effect of globin digest may be valuable for preventing obe